KMnO4‐system etching process and electroless nickel plating on ABS. Issue 4 (15th October 2018) - Chen, Shixing; Zhu, Qiyuan; Zhao, Yinghai; He, Jinmeng; Wang, Guixiang
Abstract : Etching treatment for acrylonitrile butadiene styrene (ABS) resin and electroless nickel plating process have been studied. The ABS first was etched in a chromium‐free potassium permanganate etching system with different etching times. Scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT‐IR), and hydrophilicity test showed that the ABS is of moderate and homogeneous hole size after being etched at a temperature of 65 °C with 6 g L −1 potassium permanganate for 20 min. Then electroless nickel process was performed by immersing the ABS into in a Ni plating bath at 45 °C for 20 min at a pH of 8.5–9.5. The coating was even, dense, and reveals good corrosion resistance. In addition, the nickel plating adhesion strength reached 2.73 MPa. Therefore, the excellent performance of the KMnO4 ‐H2 SO4 ‐H3 PO4 ‐H2 O etching system may replace the traditional chromic anhydride‐sulfuric acid etching system as an environmentally friendly process. Abstract : Ni‐P/ABS resins were successfully prepared via an electroless plating route in an KMnO4‐system etching solution at 65 °C for 20 min, and the optimal adhesion strength of such composites with compact nickel layers could reach 2.73 MPa.